Homo Holocaustus, or Autobiographical Female Experience of the Holocaust - Żórawska-Janik, Natalia (Tematy i Konteksty, 2021)
The aim of this paper is to present the motif of the Shoah in female autobiographcial prose after the year 2000. The paper shows that, in recent years, more and more female authors in the second and third post-Holocaust generations have been recording their traumatic experience, and that the reason for it lies in the social stigmatization of Jewish people. It is stressed here that the issues of the Holocaust are part and parcel of a cultural taboo and – similarly to female written prose – they are frequently ignored or evaluated negatively. The Holocaust issues are tackled by contemporary young writers of Jewish descent who – contrary to the previous generation authors – have not experienced the mass murder of Jews; nevertheless, they feel its effects today. This paper proves that the research into trauma studies is not really conducted in Poland, and paying attention to a female viewpoint is very rare. The examples referred to in the paper of the autobiographical novels by Ewa Kuryluk, Agata Tuszyńska, Roma Ligocka and Magdalena Tulli demonstrate that this kind of writing is becoming more and more important within the literature focused on the Shoah. Compared to the autobiographical fiction by Marek Bieńczyk, Jan Tomasz Gross and Michał Głowiński, female Holocaust stories are distinguished by their authenticity, emotionality, intimacy and honesty of narration. The stories are devoid of any pathos, and they highlight the figure of a mother. Moreover, their confessions are based on the physical feeling of the legacy which has remained in their hearts and minds after the trauma that their loved ones had to experience. An attempt to describe prose post-Holocaust prose is made in comparison to Jewish literature in Poland, drawing the reader’s attention to the characteristic features of these issues compared to the autobiographical works by men.